The Impact of Three Different Canal Lubricants on Fracture, Deformity and Metal Slivering of ProTaper Rotary Instruments - Shantiaee, Yazdan; Dianat, Omid; Sharifi, Farnoud; Nahvi, Golnaz; Kolahi Ahari, Golbarg (Iranian Endodontic Journal, 2014)
Introduction: The aim of this in vitro study was to evaluate the effect(s) of three canal lubricants i.e. sodium hypochlorite, RC-Prep as the paste form of ethylenediaminetetraacetic acid (EDTA) and aqueous EDTA, on the occurrence/incidence of fracture, deformity and metal slivering of ProTaper rotary instruments. Methods: A total of 120 mesial canals (i.e. mesiobuccal and mesiolingual) of first mandibular molars or buccal canals (i.e. mesiobuccal and distobuccal) of first maxillary molars, with curvatures of 10-20 degrees were selected and randomly divided into three groups of forty samples each. These selected canals all had approximate 19-21 mm working length and apical diameter equal to a #15 K-file. In each group, the root canals were prepared using ProTaper rotary instruments with an electric motor using one of the three aforementioned irrigants. Subsequently, samples were compared to each other at different magnifications (16×, 20×, 40× and 57×) for any fracture, deformity or metal slivering, by the Cox regression analysis. Results: The fractures rate of samples in RC-Prep group was significantly higher compared to other groups (P=0.01). No evidence of instrument deformity was detected in any groups. A statistically significant reverse relation between metal slivering and instrument fracture was observed. Conclusions: Application of aqueous EDTA and/or sodium hypochlorite as intracanal lubricants caused less fracture of ProTaper instruments compared to canal lubrication with RC-Prep.